Audio-Visual Recording Of Civil Trials As A Means To Enhance Judicial Accountability And Transparency - Angga Prihatin; Alhadiansyah; Marnita (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2026)
The implementation of audio-visual recording in court proceedings is regulated by Supreme Court Circular Letter Number 4 of 2012 on the recording of trial processes; however, its application is still restricted to corruption cases and other cases that attract significant public attention. This study examines the urgency and legal foundations for extending trial recording to civil proceedings and evaluates its role in enhancing judicial transparency and accountability. Trial recordings constitute an important innovation that should ideally be applied to all types of cases, including civil cases, so that recordings can be used by the parties in procedural processes and ensure transparent and accountable judicial decision-making. The study applies a normative juridical approach by analyzing statutory provisions, legal doctrines, and relevant scholarly literature. The results demonstrate that trial recording contributes to greater transparency of information, helps minimize the risk of misuse of authority, and reinforces public confidence in judicial institutions. Recordings also provide accurate documentation of trial proceedings, serving as a reference for the parties and assisting judges in decision-making in civil cases. Therefore, from a normative perspective, the Supreme Court must enact explicit regulation mandating audio-visual recording in civil trials as an instrument of judicial accountability and transparency.